Aryans, Jews, Brahmins : theorizing authority through myths of identity - Figueira, Dorothy Matilda, 1955- (SUNY series, the margins of literature., 2002)
In this cross-cultural study of the Aryan myth in which Brahmin Indian and European races but not Semitic ones share roots, Figueira (comparative literature, U. of Georgia) reads canons and "loose can[n]ons" in this origin myth's construction from Enlightenment and Romantic discourse to Indian reformers' anti- myths. Annotation copyrighted by Book News, Inc., Portland, OR